Assessment of bacterial viability / activity in water samples - Xie, Shuang (2010)
Rapid bacteria detection and viability / activity assessments have been greatly enhanced by recent advances in the use of fluorescent stains in flow cytometry. However, complex environmental matrices pose difficulties in assessing bacterial parameters using flow cytometry in terms of label specificity, fluorescent response, and method sensitivity.